Investment Dynamics and Earnings‐Return Properties: A Structural Approach - BREUER, MATTHIAS; WINDISCH, DAVID (Journal of Accounting Research, 2019)
ABSTRACT We propose the standard neoclassical model of investment under uncertainty with short‐run adjustment frictions as a benchmark for earnings‐return patterns absent accounting influences. We show that our proposed benchmark generates a wide range of earnings‐return patterns documented in accounting research. Notably, our model generates a concave earnings‐return relation, similar to that of Basu [1997], and predicts that the earnings‐return concavity increases with the volatility of firms’ underlying shock processes and decreases with the level of firms’ investments. We find strong empirical support for these predictions. Overall, our evidence suggests that our proposed benchmark is useful for understanding the joint dynamics of variables of interest to accounting research (e.g., earnings, returns, investment, market‐to‐book) absent accounting influences, a necessary precondition for inferring the effects of accounting from these dynamics.